The Improvement of Accreditation through Evaluation on Management Standards in Madrasah Tsanawiyah - Sukmawati Sukmawati; Yusak Ujang; Soeharto Soeharto (Journal of Educational Science and Technology (EST), 2019)
This research was a descriptive study and conducted at MTs Al-Anwar. The research process is carried out in several stages, namely: the preliminary stage, pre-field, fieldwork, research, analysis of data collected findings, data presentation, and research reports. Data collection techniques are interviews and observation with a tool to collect data on observation and documentation format. The results are obtained 1) The gap between expectations and reality on management standards; 2) Obstacles encountered in Madrasah Tsanawiyah Al-Anwar in implementing management standards, namely (a) The budget is not enough to carry out activities (RKAS) because the costs incurred are not in accordance with the plan; (b) There is no community assistance other than committee funds; (c) The number of education levels in one location has resulted in the development of madrasah tsanawiyah being hampered; (d) Adjacent to the Madrasah Tsanawiyah there are several schools around the place; 3) Efforts made by Madrasah to overcome obstacles through 1) Carry out activities in accordance with available funds; 2) The principle of openness to financial conditions to committees and teachers and staff; 3) There is BOS assistance and participating in the DNDMFN BOS, so that it can complement the needs of madrasah.